A Comparative Study of the Psychology of Color in the Contemporary Poetry of Iranian and Afghanistanian Women Based on Max Luscher's Theory; A Case Study of the Poems of Forough Farrokhzad and Khaleda Forough - Shafiullah Salik; Mahsa Rone (زن در فرهنگ و هنر)
In contemporary psychology, color is regarded as one of the personality measurement criteria. This is due to the fact that each color has a special effect on the viewer’s mind and body, representing their mental state. Poetry of the poet's entire mental and spiritual makeup, as it is derived from her emotions and sentiments. Max Luscher’s color psychology is a method that utilizes the selection of colors to gain insight into the human psyche. This investigation has examined the poetry of Forough Farrokhzad and Khaleda Forough, two contemporary poets associated with the Romantic Movement in Iran and Afghanistan, in accordance with the aforementioned theory. The quality and extent of the use of colors in their poems demonstrate that Forough Farrokhzad’s poetry prioritizes black, which reflects her inner conflicts, dissatisfaction, and disgust with the environment, as well as her depression and isolation. However, her frequent use of green in conjunction with black suggests her aspiration to alter the course of history and revolutionize society. Khaleda Forough's initial selection is green, which is a symbol of faith, freedom, and serenity. The color black, which is situated adjacent to green, is associated with tyranny, suffocation, and social unrest. The examination of the poetry notebooks of these two poets reveals that the use of calm and optimistic colors progressively replaces the use of dark colors. This demonstrates their aspiration and optimism for a more fulfilling existence, as well as their interest in implementing appropriate modifications to the image that evokes their emotions.